Ag/GO nanocatalysts for N-alkylation. (2020) - Sarno, M.; Iuliano, M.; Ponticorvo, E.
Abstract: Here we report, for the first time, the catalytic activity towards N-alkylation reactions of an Ag/GO nanocatalyst. The nanocatalyst was obtained through a "green" approach and directly used in N-alkylation of aniline, showing high conversion and selectivity in short times and mild conditions. The reusability of Ag/GO nanohybrid was also checked, showing a very small loss of activity after six consecutive cycles. The efficiency of Ag/GO nanohybrid was ascribed not only to the high availability of Ag exposed on the GO carpet, but also to the combination of silver and GO enhancing the Ag catalytic activity.